PENGARUH MOTIVASI BERWIRAUSAHA TERHADAP KEBERHASILAN USAHA BENGKEL MOTOR DI KECAMATAN TELUKDALAM KABUPATEN NIAS SELATAN - Juniar Juwita Dakhi (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
The aim of this research is to determine the influence of entrepreneurial motivation on the success of motorbike repair shops in Telukdalam District, South Nias Regency. The type of research is quantitative, the population of this research is 40 respondents. The sampling technique used is saturated sampling. The type of data for this research is primary data, while the data source for this research is from motorbike repair shops using a questionnaire. The data analysis technique is simple regression analysis. The results of the research are that there is a significant influence of entrepreneurial motivation on the success of motorbike repair shops in Telukdalam District, South Nias Regency. The suggestions for this research are (1) To increase business success, especially motorbike repair shops in Telukdalam District, the government should provide entrepreneurial motivation for every micro business actor through loans with relatively small interest to facilitate the community's economic cycle. (2) Because entrepreneurial motivation variables have a big influence on business success, every entrepreneur and related parties who determine business success need to consider this carefully.